Pelatihan Pengembangan Soal Higher Order Thinking Skill (HOTS) bagi Guru SD - Fitri Alfarisa; Supriadi Supriadi; Susilawati Susilawati; Annisa Dinur; Jamah Dini Tawana (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The results of the TIMSS survey showed that Indonesia is in a lower position than several countries in Asia. One of the alternative ways to deal with that problems is elementary school teachers' training on developing High Order Thinking Skill (HOTS) questionss. The training is a part of community service to prepare the teachers with the hots questions concept. The training also provides them with examples of mathematics and social studies hots questions. The purpose of this training is to provide an understanding of HOTS questions concept and provide examples in developing mathematics and social studies HOTS questions for teachers. The method of the training consists of material presentation and reflection sessions. In the reflection session, the elementary school teacher made and presented their hots questions. The training also is expressed in three stages; preparation, implementation, and evaluation. There are seven teachers from the Elementary School of Teaching Laboratory of UPI Serang campus as participants. They gave positive responses to the training as they got experience in developing hots questions. They also develop their knowledge in designing the questions. The output of the program is sets of mathematics and social studies HOTS questions and the journal publication.